2002
DOI: 10.1086/340100
|View full text |Cite
|
Sign up to set email alerts
|

Spotless Rickettsiosis Caused byRickettsia slovacaand Associated withDermacentorTicks

Abstract: The pathogenic role of Rickettsia slovaca was first demonstrated in 1997 in a patient who presented with a single inoculation lesion of the scalp and enlarged cervical lymph nodes after receiving a bite from a Dermacentor tick. Subsequently, we evaluated the occurrence of R. slovaca infections among patients living in France and Hungary who presented with these symptoms. R. slovaca infections were confirmed by polymerase chain reaction (PCR) in 17 of 67 enrolled patients. Infections were most likely to occur i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
137
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(151 citation statements)
references
References 24 publications
6
137
0
8
Order By: Relevance
“…The patients seen during our study experienced a mild disease typified by fever and headache, often malaise, and less frequently, a stiff neck and joint pain (7). No eschar was reported, and unlike previously reported cases of "spotless" rickettsiosis (for instance, following R. slovaca infection [36]), all our patients exhibited fever. The symptoms resolved upon treatment with doxycycline for 1 week.…”
Section: Discussionmentioning
confidence: 41%
“…The patients seen during our study experienced a mild disease typified by fever and headache, often malaise, and less frequently, a stiff neck and joint pain (7). No eschar was reported, and unlike previously reported cases of "spotless" rickettsiosis (for instance, following R. slovaca infection [36]), all our patients exhibited fever. The symptoms resolved upon treatment with doxycycline for 1 week.…”
Section: Discussionmentioning
confidence: 41%
“…This bacterium was isolated in 1968 from D. marginatus ticks in Czechoslovakia. In 1997, R. slovaca was described as a human pathogen and the agent of tick-borne lymphadenopathy (TIBOLA), also known as Dermacentor-borne necrotic erythema and lymphadenopathy (DEBONEL), which is defined as the association of a tick bite, an inoculation eschar on the scalp, and cervical lymphadenopathies (Raoult et al, 2002b (Mediannikov et al, 2008). R. raoultii was detected in ticks collected from several European countries: France, Russia, Poland, Slovakia, Spain, Portugal, Germany, Croatia and the Netherlands (Dobler & Wolfel, 2009;Ibarra et al, 2005;Matsumoto et al, 2009;Vitorino et al, 2007;Nijhof et al, 2007;Mediannikov et al, 2008).…”
Section: Rickettsia Massiliaementioning
confidence: 99%
“…conorii has long been considered to be the only SFG rickettsiosis but R . slovaca may also be prevalent ( 9 ), contributing 25% of the cases in the present study. This organism is also a common cause of disease in Hungary and in La Rioja, Spain ( 3 ).…”
mentioning
confidence: 49%
“…This organism is also a common cause of disease in Hungary and in La Rioja, Spain ( 3 ). These data suggest that TIBOLA mainly occurs in young children, affects women predominately, and occurs primarily during the colder months ( 9 , 10 ). As previously reported ( 9 ), we found that standard microimmunofluorescence serologic testing was insensitive and that Western blot is more useful and allows identification to the species level after cross-adsorption studies.…”
mentioning
confidence: 79%
See 1 more Smart Citation